Community psychology and oral history in Eldorado Park: A case study in surveillance, confession and resistance - Terre Blanche, Martin (My University, 1994)
Psychologists have a reputation for individualising, decontextualising and depoliticising human suffering. Despite numerous exceptions to this rule - e.g. the attempts to theorize colonial and class oppression by Fanon (1978), Bulhan (1985), Manganyi (1991) and others - it remains true that many psychologists choose to confine their work (and their thinking) to the safe world of the consulting room and the laboratory. Even the two branches of the discipline supposedly most concerned with social issues - social psychology and community psychology - are notorious for their persistent individualising tendencies. In this paper we describe and critique a community psychology initiative, in which we are involved, which attempts to move beyond the individual as level of analysis and target for intervention. In particular we are concerned to show how the knowledge produced in and about communities through such initiatives constitutes an exercise of disciplinary power, and to question whether such power may be wielded in a beneficial manner.
African Studies Seminar series. Paper presented 3 October 1994
Keywords: Community psychology. South Africa. Case studies.; Oppression (Psychology)